Potential for immune-driven viral polymorphisms to compromise antiretroviral-based preexposure prophylaxis for prevention of HIV-1 infection. (10th September 2017) - Gatanaga, Hiroyuki; Brumme, Zabrina L.; Adland, Emily; Reyes-Terán, Gustavo; Avila-Rios, Santiago; Mejía-Villatoro, Carlos R.; Hayashida, Tsunefusa; Chikata, Takayuki; Van Tran, Giang; Van Nguyen, Kinh; Meza, Rita I.; Palou, Elsa Y.; et al.
Abstract : Objective: Long-acting rilpivirine is a candidate for preexposure prophylaxis (PrEP) for prevention of HIV-1 infection. However, rilpivirine resistance mutations at reverse transcriptase codon 138 (E138X) occur naturally in a minority of HIV-1-infected persons; in particular those expressing human leukocyte antigen (HLA)-B * 18 where reverse transcriptase-E138X arises as an immune escape mutation. We investigate the global prevalence, B * 18-linkage and replicative cost of reverse transcriptase-E138X and its regional implications for rilpivirine PrEP. Methods: We analyzed linked reverse transcriptase-E138X/HLA data from 7772 antiretroviral-naive patients from 16 cohorts spanning five continents and five HIV-1 subtypes, alongside unlinked global reverse transcriptase-E138X and HLA frequencies from public databases. E138X-containing HIV-1 variants were assessed for in-vitro replication as a surrogate of mutation stability following transmission. Results: Reverse transcriptase-E138X variants, where the most common were rilpivirine resistance-associated mutations E138A/G/K, were significantly enriched in HLA-B * 18-positive individuals globally ( P  = 3.5 × 10 −20 ) and in all HIV-1 subtypes except A. Reverse transcriptase-E138X and B * 18 frequencies correlated positively in 16 cohorts with linked HIV/HLA genotypes (Spearman's R  = 0.75; P  = 7.6 × 10 −4 ) and in unlinked HIV/HLA data from 43 countries (Spearman's R  = 0.34, P  = 0.02). Notably, reverse transcriptase-E138X frequencies approached (or exceeded) 10% in key epidemic regions (e.g. sub-Saharan Africa, Southeastern Europe) where B * 18 is more common. This, along with the observation that reverse transcriptase-E138X variants do not confer in-vitro replicative costs, supports their persistence, and ongoing accumulation in circulation over time. Conclusions: Results illustrate the potential for a natural immune-driven HIV-1 polymorphism to compromise antiretroviral-based prevention, particularly in key epidemic regions. Regional reverse transcriptase-E138X surveillance should be undertaken before use of rilpivirine PrEP. Abstract : Supplemental Digital Content is available in the text